Level Of Psychosocial Wellbeing Among Mothers Of Children Admitted To Selected Icus - H K, Komala; Nalini M, Nalini M; K S, Chandravathi (Journal of Neonatal Surgery, 2025)
Background: A maternal bond is the relationship between a mother and her child. The mothers’ psychosocial wellbeing is crucial because it directly influences their ability to cope with the situation, their interactions with healthcare providers, and their capacity to care for their child. Additionally, the mental health of mothers can have significant secondary effects on the child’s health and recovery process. For instance, a mother’s psychological distress can impact her capacity to provide optimal emotional and practical care for her child during and after their ICU stay. Methodology: The research design used in this study was the descriptive design. 30 mothers were selected by Non- probability convenience sampling technique. The tools used for data collection was a The DASS-42 is a 42 item self-report scale designed to measure the emotional states of depression, anxiety and stress. Results: The study revealed that 83.3% of the subjects have extremely sever depression and 16.7% have severe depression and there is no moderate , mild and normal depression. 100% of the subjects have extremely sever level of anxiety. And 40% of the subjects have extremely sever level of and 56.7% have severe level of stress and 3.3% have moderate level of stress. Conclusion: The findings of the study concluded that mothers have poor psychosocial wellbeing.